An Empirical Investigation of Parasocial Relationship Theory in the Context of Virtual Influencers - Shaji, Rooth (2024)
A Master of Business Administration (MBA) thesis by Rooth Shaji entitled, “An Empirical Investigation of Parasocial Relationship Theory in the Context of Virtual Influencers”, submitted in December 2024. Thesis advisor is Dr. Jeff Baker and thesis co-advisor is Dr. Kichan Nam. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).